Model-Based Control Design of Series Resonant Converter Based on the Discrete Time Domain Modelling Approach for DC Wind Turbine - Chen, Yu-Hsing; Dincan, Catalin Gabriel; Kjær, Philip; Bak, Claus Leth; Wang, Xiongfei; Imbaquingo, Carlos Enrique; Sarrà, Eduard; Isernia, Nicola; Tonellotto, Alberto (Journal of Renewable Energy, 2018)
This paper focuses on the modelling of the series resonant converter proposed as a DC/DC converter for DC wind turbines. The closed-loop control design based on the discrete time domain modelling technique for the converter (named SRC#) operated in continuous-conduction mode (CCM) is investigated. To facilitate dynamic analysis and design of control structure, the design process includes derivation of linearized state-space equations, design of closed-loop control structure, and design of gain scheduling controller. The analytical results of system are verified in z-domain by comparison of circuit simulator response (in PLECS™) to changes in pulse frequency and disturbances in input and output voltages and show a good agreement. Furthermore, the test results also give enough supporting arguments to proposed control design.